A magnetic nanoadsorbent based on expanded graphite with enhanced surface area for the removal of sulfamethoxazole and malachite green from aqueous solutions - Asadollah Mohammadi; Parisa Abedi; Mohammad Reza Gholami (Journal of Water and Environmental Nanotechnology)
In this study, a new magnetic nanoadsorbent (denoted as Fe3O4/EXG/Cellulose) was synthesized using expanded graphite (EXG), microcrystalline cellulose and Fe3O4 nanoparticles. The Fe3O4/EXG/Cellulose was used as an effective nanoadsorbent for the removal of sulfamethoxazole (SMX) and malachite green (MG) from aqueous solutions using batch process. The Fe3O4/EXG/Cellulose was fully characterized by the Fourier transform infrared (FT-IR), X-ray diffraction (XRD), Energy-dispersive X-ray spectroscopy (EDX), Brunauer-Emmett-Teller (BET), Field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM) analyses. Based on the BET analysis, an improved surface area from 10.32 to 71.86 m2 g–1 was achieved after the modification of expanded graphite using microcrystalline cellulose. The adsorption capacities for the MG dye and SMX drug were determined to be 109.9 and 3.9 mg/g, respectively. In addition, the adsorption process of SMX and MG by the Fe3O4/EXG/Cellulose was studied with isotherm and kinetic models. The results indicate the adsorption of SMX and MG by nanocomposite better described with pseudo-second-order kinetic. In addition, Langmuir and Freundlich isotherm models well describe the adsorption of MG and SMX using Fe3O4/EXG/Cellulose, respectively. Furthermore, Fe3O4/EXG/Cellulose can be easily recycled and reused for over 5 times and keeps a high level of adsorption efficiency.